Brainstem volumetric integrity in preclinical and prodromal Alzheimer’s disease - Dutt, Shubir (J Alzheimers Dis, 2020)
BACKGROUND: Neuropathological studies have suggested the tau pathology observed in Alzheimer’s disease (AD) originates in brainstem nuclei, but no studies to date have quantified brainstem volumes in clinical populations with biomarker-confirmed mild cognitive impairment (MCI) or dementia due to AD or determined the value of brainstem volumetrics in predicting dementia. OBJECTIVE: The present study examined whether MRI-based brainstem volumes differ among cognitively normal older adults and those with MCI or dementia due to AD and whether preclinical brainstem volumes predict future progression to dementia. METHODS: Alzheimer’s Disease Neuroimaging Initiative participants (N = 1,629) underwent baseline MRI scanning with variable clinical follow-up (6–120 months). Region of interest and voxel-based morphometric methods assessed brainstem volume differences among cognitively normal (n = 814), MCI (n = 542), and AD (n = 273) participants, as well as subsets of CSF biomarker-confirmed MCI (n = 203) and AD (n = 160) participants. RESULTS: MCI and AD cases showed smaller midbrain volumes relative to cognitively normal participants when normalizing to whole brainstem volume, and showed smaller midbrain, locus coeruleus, pons, and whole brainstem volumes when normalizing to total intracranial volume. Cognitively normal individuals who later progressed to AD dementia diagnosis exhibited smaller baseline midbrain volumes than individuals who did not develop dementia, and voxel-wise analyses revealed specific volumetric reduction of the locus coeruleus. CONCLUSION: Findings are consistent with neuropathological observations of early AD-related pathology in brainstem nuclei and further suggest the clinical relevance of brainstem substructural volumes in preclinical and prodromal AD.